The mining of cobalt must meet the highest environmental and health standards - Michael NA Eskin (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
In an effort to combat climate change there is a major rush to eliminate the use of fossil fuels. However, this must be done in an orderly process to avoid stressing an already overstressed planet. The push for electric cars and lithium batteries requires intensive mining to extract the heavy metals needed to meet increasing global demands. This is in addition to the already staggering increase in the worldwide usage of digital devices and electronics that require the same metals. Heavy metals such as nickel, chromium, iron, zinc, manganese and cobalt, at very low concentrations, are all essential to the growth and development of plants [1-3].